Introduction to the philosophy of the human person - Abella, Roberto D. (C & E Publishing, Inc., 2016)
"This textbook endeavors to introduce Senior High School students to the study of Philosophy as an exploration of the fundamental questions and issues that have faced humanity throughout history. It traces the significant views and developments as Philosophy unfolded through the ages, and endeavors to relate important philosophical questions, theories, and views to life's experiences. It also aims to help students better understand themselves and the world they live in and enable them to navigate through the challenges of life. In addition, the discussion also highlights the spiritual dimension of human existence and seeks a balance between the humanist and spiritual perspectives in facing personal issues and understanding experiences." -- Preface.